Persepsi masyarakat Desa Jake Kelurahan Simpang Tiga Kuantan Singingi terhadap penggunaan kain pembungkus furoshiki sebagai budaya baru melalui pelatihan PkM - Yenny Aristia Nasution; Sri Wahyu Widiati; Hana Nimashita; Adisthi Martha Yohani (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
Introducing furoshiki culture to the community is one of the efforts to preserve the environment. Furoshiki with high aesthetic value is expected to attract the community's attention and encourage its use as a substitute for plastic packaging. Through the Community Service (PkM) activity organized by the Japanese Language Education Study Program, FKIP, Riau University, an introduction to the history and culture of furoshiki, the practice of using furoshiki, and distributing questionnaires was carried out to determine the community's perception of the potential for accepting furoshiki as a new culture and habit in the local community. The target community was 50 members of the PKK of Jake Village, Simpang Tiga Village, Kuantan Tengah District, Kuantan Singingi Regency, Riau Province. From the results of the questionnaire, 100% of participants agreed to practice the use of furoshiki, 98% agreed to accept furoshiki as a new culture, 100% supported the efforts and means of spreading furoshiki, and 90% were interested in it. Based on these results, it can be said that the community can easily accept furoshiki culture as part of everyday life. However, to achieve optimal sustainability, efforts are needed to introduce furoshiki culture more widely in society and to adopt its use consistently